Cost-Benefit Analysis of Types of Trucking Utilized by SEPI: Basis for Action Plan - Sarmiento, Michael G.; Bucal, Remedios J.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
The study evaluates the cost-benefit analysis between company-owned fleets and outsourced trucking at SEPI, a manufacturing firm in Laguna. As of 2024, SEPI’s truck usage consists of 62% company-owned and 38% outsourced. Due to aging trucks, maintenance is outsourced, leading to increased operating expenses (OpEx), including fuel, repairs, insurance, and salaries. The lack of prior analysis raises the question of whether investing in new trucks or continuing outsourcing would be more cost-effective. Using literature and surveys, the research analyzed Capital Expenditures (CAPEX), Operating Expenses (OPEX), and benefits such as Efficiency, Cost-Savings, Risk, and Operational Flexibility for both trucking options. Results showed that outsourced trucking had lower costs and provided greater benefits for SEPI. The study applied Transaction Cost Economics (TCE) and Resource-Based View (RBV), utilizing a descriptive comparative design with stratified random sampling and online surveys rated on a 4-point Likert scale. Findings revealed that company-owned fleets had higher cost ratings (CAPEX: 3.13, OPEX: 3.03), whereas outsourced trucking had moderate cost ratings (2.23 for CAPEX, 2.17 for OPEX). Additionally, outsourced trucking scored higher in Efficiency (3.34), Cost-Savings (3.33), Risk (3.28), and Operational Flexibility (3.39), demonstrating a more favorable outcome. In conclusion, outsourcing offers SEPI significant advantages, including lower capital investments, reduced operational costs, and improved focus on product quality and core business functions.